2009
DOI: 10.1128/aac.00815-09
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Antibiotic Hybrid Nanoparticles for Targeting Intracellular Pathogens

Abstract: We investigated the capability of biodegradable silica xerogel as a novel carrier of antibiotic and the efficacy of treatment compared to that with the same dose of free drug against murine salmonellosis. The drug molecules (31%) entrapped in the sol-gel matrix remained in biologically active form, and the bactericidal effect was retained upon drug release. The in vitro drug release profiles of the gentamicin from the xerogel and that from the xerogel-polyethylene glycol (PEG) were distinctly different at pH 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 25 publications
2
48
0
1
Order By: Relevance
“…17 Furthermore, nanoparticles can mask the entrapped drug, reducing systemic toxicity induced by conventional administration of the free drug. 18 Moreover, polymeric nanoparticles have shown to enhance the oral bioavailability of orally inactive antibiotics. 13 PLGA polymers have been used to entrap several antibiotics in nanoparticle formulations, demonstrating improved delivery and antibiotic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, nanoparticles can mask the entrapped drug, reducing systemic toxicity induced by conventional administration of the free drug. 18 Moreover, polymeric nanoparticles have shown to enhance the oral bioavailability of orally inactive antibiotics. 13 PLGA polymers have been used to entrap several antibiotics in nanoparticle formulations, demonstrating improved delivery and antibiotic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that by incorporation of PEG the drug release can be modulated. Administration of two doses of the xerogel formulations showed a remarkable reduction in the load of Salmonella entrica in the spleen and liver of the infected mice (86). A similar study was performed by another group on gentamicin silica xerogel systems showing that the silica xerogel was more effective in clearing the infection in the liver compared to the same dose of the free drugs (87).…”
Section: Xerogel Systems Containing Antibioticmentioning
confidence: 60%
“…During the last fifteen years, a special attention has been dedicated on silica xerogel system to treat diseases due to intracellular pathogens (86)(87)(88)(89)(90)(91)(92). The properties of silica xerogel systems such as size, zeta potential, pore structure, and the surface characteristics make them suitable carriers for therapeutics to target the replicative niche of intracellular pathogen.…”
Section: Xerogel Systems Containing Antibioticmentioning
confidence: 99%
“…The effects of long-term nanoparticle accumulation are unknown, so in many cases it may be better to use a material that is fully biodegradable. Silica-based compounds are another option, as the biodegradation of silica avoids tissue accumulation concerns, 98 and it has been demonstrated that a variety of agents have been successfully incorporated into silica-based nanoparticles [99][100][101] for drug delivery applications. Although each of these materials offers its own set of characteristics and biocompatible properties, some materials may be more suited to certain applications than others.…”
Section: Biocompatibility and Nanotoxicitymentioning
confidence: 99%
“…75 Nanoparticles have been fabricated using a variety of materials, including poly(lactide-co-glycolide) (PLGA); [76][77][78][79][80][81] [98][99][100][101] PLGA has been approved by the Food and Drug Administration for several biomedical applications, including surgical sutures, implants, and prosthetic devices. 78 PLGA micro-or nanoparticles have also been used for a variety of drug delivery applications.…”
Section: Biocompatibility and Nanotoxicitymentioning
confidence: 99%